Resetting International Law Linkages: COP 20 Mechanisms and Protocols - Ferrey, Steven (2014)
The article reviews the experiences of programs to promote renewable energy in Southeast Asian countries and proposes some learned lessons that can be useful in the context of COP 20 to promote renewable energy.The article analyzes the rates and mechanisms of promotion used in countries such as India, Indonesia and Vietnam, that are led by the World Bank. These mechanisms are used as a legal basis that proposes successful tested alternatives and its usefulness is that renewable energies can be implemented within the current legal structure of international environmental law.In conclusion, it is the correct timing for the COP 20 to secure funds and international legal mechanisms that promote sustainable energy infrastructure.